2012
DOI: 10.3109/07435800.2012.713425
|View full text |Cite
|
Sign up to set email alerts
|

IL-1αand IL-1βLevels in Blood Serum and Saliva of Menopausal Women

Abstract: There were no significant differences in the concentrations of interleukins in the various research groups. The results of densitometric analysis showed a positive impact of hormone replacement therapy on the BMD (0.91-0.92 g/cm2) compared with the density in the group not treated with hormone therapy (0.77-0.8 g/cm2). There was no relationship between concentration of interleukins and the level of BMD. CONCLUSIONS. Further research on the level of cytokines in serum and saliva conducted on a broader group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Under such conditions, salivary inflammation increases due to higher local production of inflammatory factors and possibly an increased infiltration from blood (Bosch, 2014). Several studies have reported substantially higher levels of inflammatory markers in saliva than in blood (Khan, 2012; Miller et al, 2010; Rahnama et al, 2013), further supporting the notion that salivary cytokines are being produced by local tissues in lieu of (or in addition) to their infiltrating the mouth from the periphery (i.e., from blood). Importantly, a vast majority (>80%) of adults in the United States exhibit gingivitis in one or more teeth, and almost 50% of individuals over age 50 present with some level of periodontal disease (Albandar, 2002).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Under such conditions, salivary inflammation increases due to higher local production of inflammatory factors and possibly an increased infiltration from blood (Bosch, 2014). Several studies have reported substantially higher levels of inflammatory markers in saliva than in blood (Khan, 2012; Miller et al, 2010; Rahnama et al, 2013), further supporting the notion that salivary cytokines are being produced by local tissues in lieu of (or in addition) to their infiltrating the mouth from the periphery (i.e., from blood). Importantly, a vast majority (>80%) of adults in the United States exhibit gingivitis in one or more teeth, and almost 50% of individuals over age 50 present with some level of periodontal disease (Albandar, 2002).…”
Section: Discussionmentioning
confidence: 69%
“…The studies that have focused on correlations between salivary and blood-based inflammation have been conducted with static, baseline levels (i.e., not in response to stress) (Rahnama et al, 2013; Williamson et al, 2012). Salivary inflammatory cytokines may perhaps relate better to blood-based cytokines in the context of stress responses, and/or if examined on a lagged time basis from systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases the feeling of dryness in only a subjective complaint and the examination of salivary flow and status of oral mucosa does not reveal abnormalities. In the present study women who complained of mouth dryness were free from ulcerations or severe oral inflammations [ 17 , 18 ]. It should also be noted that saliva is essential in the process of flavour recognition.…”
Section: Discussionmentioning
confidence: 99%
“…We previously suggested a significant association between salivary IL-1β and state anger score, supporting that mediators at a local site, as mouth, may indirectly influence emotional processing and changes in motivational state 28 . Likewise, the relationship of salivary IL-6 to psychosocial stress has successful previously demonstrated 21 , 22 . Interestingly, an important role for IL-18 has been proposed in the stress response.…”
Section: Introductionmentioning
confidence: 94%
“…Studies that have focused on correlations between salivary and blood-based inflammation were mainly conducted with static, baseline levels (i.e. not in response to stress) 22 , 23 . Nowadays, within the molecules involved in the inflammatory process, a moderate to strong association has been established only for the non-specific marker of the inflammation, C-reactive protein (CRP), between its serum and salivary levels (r = 0.72, p < 0.001) in non stressful context.…”
Section: Introductionmentioning
confidence: 99%